Emerging Trends in China's Development of Unmanned Systems - Chase, Michael S. (RAND Corporation, 2015)
RAND's exploratory analysis of China's development and use of unmanned systems focuses on identifying sources related to maritime unmanned systems; understanding the roles that China sees for such systems; analyzing trends in Chinese development of unmanned vehicles; exploring how China could employ such systems in its territorial disputes in the East and South China Seas; and identifying areas for further research and potential developments.